PUBLIC PARTICIPATION IN CORRUPTION PREVENTION THROUGH IMPLEMENTATION OF E GOVERNMENT - Saadah; Verdania Latif, Dini (International Journal of Psychosocial Rehabilitation, 2020)
Corruption can cause financial losses for the state. State expenditure will be greater because of the mark up and government revenue through taxes will also be smaller. To prevent corruption the government has implemented a web-based application system, e government. The implementation of e government can increase public participation as citizen control in monitoring government activities. Public interest as citizen control is also supported by its understanding of the impact of corruption. This study aims to determine the effect of e-government implementation on the level of community participation as citizen control by using an understanding of the impact of corruption by the public as a moderating variable. This type of research is explanatory with a sample of 100 Bandung residents. This research uses regression analysis to analyze data. The results showed that the implementation of e government affected public participation as citizen control. This relationship is strengthened by the variable of citizens’ understanding of the impact of corruption